Pudricion radicular del garbanzo por el hongo Fusarium solani (Mart) Sacc - Alvarez A, M.=700 1 Briner G, C.
(En, Es)
Ilus., 6 ref
Keywords: GARBANZO; PODREDUMBRES; RAICES; FUSARIUM SOLANI; CHILE; AGRICULTURA TECNICA